The popularity of new media over old media - Yong, Lowena Xin Yi (2024)
This study investigates the increasing preference for new media platforms, including social media, online news, and streaming services, over old media sources such as radio, newspapers, and television. An online survey, created with Google Forms, was distributed to 50 respondents aged 18 to 34, capturing insights into media consumption habits, demographic backgrounds, and perceptions of both new and traditional media. Qualitative analysis methods were used to interpret the data, with Microsoft Excel facilitating the organization and categorization of responses. Excel's analytical functions allowed for the identification of key patterns and themes, shedding light on factors influencing the shift toward new media. The findings aim to reveal reasons behind these evolving media preferences and to illustrate how changes in media consumption impact interaction, communication, and perception among younger generations. By examining this shift, the study provides a comprehensive view of the media landscape's transformation and its broader implications.